Concurrent change in serum cholinesterase activity and midregional-proadrennomedullin level could predict patient outcome following liver transplantation - Decker, Sebastian; Krüger, Albert; Wilk, Henryk; Uhle, Florian; Bruckner, Thomas; Hofer, Stefan; Weigand, Markus A.; Brenner, Thorsten; Živković, Aleksandar (Biomolecules, 2022)
Background: After liver transplantation (LTX), patients are susceptible to opportunistic infections resulting in reduced outcomes within the early post-transplantation period. The postoperative monitoring of LTX patients has gained much importance in recent years. However, reliable plasmatic markers predicting 90-day outcomes are still lacking. Methods: In the post hoc analysis of a prospective, observational study, butyrylcholinesterase (BChE), mid-regional proadrenomedullin (MR-proADM), as well as conventional inflammatory markers (procalcitonin, C-reactive protein) were evaluated in 93 patients at seven consecutive timepoints within the first 28 days following LTX. Results: Persistently reduced activity of BChE and elevated MR-proADM levels indicated reduced 90-day survival following LTX. Furthermore, reduced BChE and increased MR-proADM activity could indicate early post-transplantation bacterial infections, whereas conventional inflammatory biomarkers showed no diagnostic efficacy within the observation period. Conclusion: Concurrent assessment of BChE and MR-proADM activity might serve as a bedside diagnostic tool for early bacterial infections following liver transplantation. Thus, a combined utilization of the two biomarkers may be a useful tool in the risk evaluation of patients following liver transplantation.
Gesehen am 19.08.2022